The Numerical and Experimental Investigation of Heat Transport and Water Infiltration in Granular Packed beds due to Supplied Hot Water (One-and Two-Dimensional Models) - Rattanadecho, P.; Wongwises, S. (Science & Technology Asia, 2015)
-